Students’ Needs on Development Programs: Inputs for Student Services Enhancement - Wilter Friales; Ian Jay C. Sunio; Quennie Marie Zuyco; Riza Mae Carreon (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study assessed needs for development programs of NDMU students in terms of leadership formation, socio-cultural performing arts, advocacy programs, involvement in clubs and organizations, and sports and wellness programs. It was conducted at Notre Dame of Marbel University with 345 respondents enrolled in the school year 2019-2022 and was selected through convenient sampling. Researcher- made on needs assessment survey questionnaire was employed and online survey method was used in gathering the data. This study also utilized a quantitative-descriptive research design using descriptive statistics in analyzing the data. The mean was used to determine the degree of involvement of students in different categories. Data revealed that there is a high degree of need to address the leadership and formation of students with an overall mean of 3.30. Also, in socio-cultural and performing arts, it was found out that there is moderate degree of need to intensify the program that will help the students improve their skills in performing, with an overall mean of 3.10. In terms of the advocacy program, there is a moderate degree of need to enhance the social and communication skills of the students who wanted to organize community projects, with an overall mean of 3.23. Further, the data gathered showed that the involvement in the clubs and organizations of the students has a moderate degree of need to be improved with an overall mean of 3.20, and when it comes to sports and wellness, there is a moderate degree of need to intensify, or address with an overall mean of 3.19. Since there is a high degree of need for leadership and formation, there is a need to strengthen the activities involved in this category. On the other hand, four (4) categories were assessed as having moderate need; there is also a need to re-visit and evaluate to justify making these programs more effective.